Decentralization, Governance and Provision of Public Goods and Services in Togo - Ayenagbo, Kossi (Advances in Social Sciences Research Journal, 2023)
The objective of this work is to analyse the impact of decentralisation on the quality of public services in Togo since 2019. After an exploratory analysis, data from the Afrobarometer survey (Round 8) were subjected to an econometric analysis with endogenous dichotomous variables. Overall, the results show that decentralisation and the level of corruption have a positive and significant impact on the quality of public service provision in Togo. The results also reveal that the accountability of local officials elected and the level of corruption have a positive and significant impact on the efficient provision of public services. These results also show that decentralisation contributes significantly to improving the quality of public services. Policy makers need to take adequate initiatives to make the transfer of competences to local governments more effective and sustainable in order to foster more inclusive development.